Experimental evaluation of a new ring esophageal ligation - Crestanello, Francisco; Beguiristain, Alberto; Lizaso, Isabel; Noguera, Gustavo; Ressia, Oscar; Pizzarossa, Carlos (Cirugía del Uruguay, 1975)
The authors report a new ring of esophageal ligature for the treatment of hemorrhage due to rupture of esophageal varices. It is based in the principie of Prioton's ring. Both the ring and its ring-holder handle, are of an original design and national manufacture. The description of the instrument is performed. Several points are experimentally evaluated: a) its handling, which is simple. The necessary care that must be taken care of, is pointed out. b) the effects of the presence of the ring in the esophagus. It is concluded that it does not require complementary techniques in order to protect the ligature, and it does not provoke fistulae or esophagitis due to reflux, and ii does not leave a scar that may lead to esophageal stenosis.